Financial institutions and private rented housing - Kemp, P; Crook, T (Joseph Rowntree Foundation, 1999)
Many UK and overseas financial institutions are now actively interested in providing both loans and equity funding for private rental housing. Building on a 1994 study, new research, by Prof. Tony Crook of the University of Sheffield and Prof. Peter Kemp of the University of Glasgow, shows that there has been a marked change in attitudes among City institutions in the last five years, although there are still important barriers to large-scale funding. •Building societies and banks are concentrating on lending, not equity investment. They are now offering longer loans and lower lending margins. Investment banks are also prepared to arrange finance, provided propositions are large enough to seek funds on the capital market. •In contrast to five years ago, pension funds and life companies are actively considering investing. Some have already done so and are buying residential portfolios. Those still examining the possibility are interested in indirect investment rather than direct ownership. •A key barrier to indirect investment is the lack of suitable investment vehicles. Many institutions had investigated Housing Investment Trusts (HITs), but felt the returns were too low, HITs were not sufficiently tax transparent, and were too complicated and restricted. •Some investment barriers had become less important, e.g. political risk, but some were still obstacles, e.g. poor liquidity. Institutions were also aware of previously unconsidered problems, e.g. poor housing management. •The lack of adequately sized residential property companies in which to invest or from which portfolios could be bought is another barrier. Most companies are too small to satisfy financial institutions' minimum funding requirements and to generate economies of scale and the returns needed. •A further barrier is the dearth of information. Institutions needed adequate, regular and sufficiently geographically disaggregated market information. •Existing property companies have few problems obtaining finance, but overseas institutions have a better understanding of the business and give better terms than UK ones. But the researchers conclude that new vehicles are needed if the new institutional interest in private rented housing is to lead to significant growth in the sector.